Characteristics of ice cream from black soybean sprout juice – red dragon fruit with yolk emulsifier - Rahayu, Wahidah Mahanani; Mustaqim, Luthfi; Khairi, Amalya Nurul; Permadi, Adi; Hidayah, Nurul (Universitas Ahmad Dahlan, 2024)
Black soybean germination into sprouts reportedly improved nutrition digestibility and bioactive compound content. Red dragon fruit (RDF) and egg yolk (EY) can be used as natural and halal colorants and emulsifiers. Black soybean sprout (BSS) juice made non-dairy ice cream with red dragon fruit and egg yolk as an emulsifier. This research aimed to measure the effect of various red dragon fruit and egg yolk concentrations on the characteristics of ice cream made from BSS juice. A completely randomized design was applied to six formulations made using the ratio of RDF : EY of FA (20%: 3%), FB (20%: 4%), FC (20%: 5%), FD (40%: 3%), FE (40%: 4%), and FF (40%: 5%). BSS juice was made using 48 hours of room temperature incubated sprout and water at a 1:4 (b/v) ratio. Filtrate was then mixed with sugar, cornstarch, and salt into a dough, which was then mixed with RDF and EY at various concentrations. Nutritional proximate composition, radical scavenging activity, phenolic content, total anthocyanin content, vitamin C, and sensory acceptance were analyzed. Data was then statistically analyzed using one-way ANOVA, followed by Duncan’s Multiple Range Test. Results showed that higher RDF significantly changed overrun, melting rate, increased moisture content, vitamin C (20.4 – 40.23 mg/100 g), antioxidant activity (34.9 – 62.78 % radical scavenging activity), total phenolics (0.341 – 0.536 mg/g GAE), and total anthocyanin (3.905 – 9.726 mg/kg), and hedonic score, but shorter melting time. The shortest melting time was obtained by ice cream made using 20% RDF and 5% EY, the lower concentration of fruit, and the highest concentration of egg yolk, respectively. The results indicated that BSS juice could be used as the main ingredient to make non-dairy ice cream, with red dragon fruit and egg yolk as natural colorants and emulsifiers, respectively. Keywords: Black soybean sprout, Non-dairy ice cream, Red dragon fruit